National Income and Its Distribution - Bruckner, Markus (IMF Working Papers; Working Paper ;, 2014)
Does the distribution of income within a country become more equal as it grows richer? This paper uses plausibly exogenous variations in trade-weighted world income and international oil price shocks as instruments for within-country variations in countries real GDP per capita to examine this issue for a large sample of advanced and developing countries. Our findings indicate that increases in national income have a significant moderating effect on income inequality: a one percent increase in real GDP per capita, on average, reduces the Gini coefficient by around 0.08 percentage points, a result that is robust across income levels, different time horizons, and alternative estimation techniques. From a policy perspective, our results suggest that education policies that promote equity and help individuals continue on to higher levels of education could help reduce income inequality.